Perancangan E-Customer Relationship Management Pada Pt Starsindo Logistics - Nelly Nelly; Hudiarto Hudiarto; Rangga Yudhika (Bina Nusantara University, 2010)
Starsindo Logistics Inc. (SL) is a company in freight forwarding service. The problem in this company is less information provided to customers, especially about customer order status information. It is started from the departure of the EMKL truck until the standard time of customer container entering freight process. Therefore, it is needed to use the customer service application electronic-Customer Relationship Management (e-CRM), because it will ease to manage and control information flow about the customer order status. The research method is following rules in object oriented analysis and design by Mathiassen. Through website, public is hoped to easily access the company information or ship schedule, order list, tracking order status, or transaction history. This web-based customer service application could help the company to build a good relationship with customers.